UPAYA PENINGKATAN PENGETAHUAN HIPERTENSI KEPADA LANSIA DI PUSKESMAS NAMORAMBE - Linta Meliala; Anggun Syafitri; Puji Lestari; Atika Patnisuri (INSTITUT KESEHATAN DELI HUSADA, 2023)
Promotive health development is one way to increase public knowledge. Hypertension is a condition that is often found and is the highest cause of death in the world. Hypertension is a condition that is often found and is the highest cause of death in the world. The purpose of this community service activity is for the community to have, understand and maximize knowledge about hypertension. The method carried out is in the form of two-way counseling using a power point instrument containing hypertension material and questionnaires before and after counseling. The target of this activity is the village community of 30 people. The implementation time will be on Saturday, June 10, 2023, located at the Namorambe Health Center. After counseling activities and questionnaire tests, it showed an increase in public knowledge about hypertension to 82%. Increasing good knowledge is expected to make people more aware and able to apply this knowledge in their daily lives.